Physicochemical properties of aqueous solutions of sodium l -prolinate as an absorbent for CO2 removal - Shaikh, M.S. (2014)
The physicochemical properties such as density, viscosity, and refractive index of aqueous solutions of sodium l-prolinate (SP) as a solvent for CO 2 capture was measured. These properties were measured at different temperatures from (298.15 to 343.15) K. The mass fractions of SP were 0.05, 0.10, 0.20, 0.30, and 0.40. The coefficient of thermal expansion was calculated from the experimental density values in the same temperature range. The analysis of experimental results shows that the densities, viscosities, and refractive indices of the aqueous solutions of SP increase with an increase in the mass fraction in the solution, and decrease with increasing temperature. The thermal expansion coefficient slightly increases with increasing temperature and concentration. The experimental data of density, viscosity, and refractive index were correlated by the least-squares method as a function of temperature. The predicted data were estimated from correlation coefficients for all measured properties and reported with standard deviations. Â© 2013 American Chemical Society.